Simulation On The Effect Of Water Absorption On The Strength Of Masonry Wall - Chow , Shiao Teng (2006)
Unit water absorption is an important characteristic in the construction of masonry structure as it plays a significant role in strength and durability performance. The moisture transfer mechanism between mortar joint and brick unit would lead to a reduction in the water content of fresh mortar, thereby causing shrinkage and moisture expansion in mortar and brick unit, respectively. In addition, poor and porous mortar joint would be produced. This would affect the masonry’s strength, durability, serviceability and cause frost damage in seasonal regions. This research was carried out to develop a new model for predicting the compressive strength of masonry wall considering the unit water absorption, unit strength and mortar strength as well as to simulate the effect of water absorption on the strength of masonry wall and to compare the developed model with other established models. Experimental investigation was conducted on 60 specimens (individual bricks and brickwork prisms made up of calcium silicate, clay and cement sand bricks) in obtaining the brick’s compressive strength, mortar strength, unit water absorption and initial rate of absorption. Based on the test results, empirical modelling of the masonry wall compressive strength with regression analysis was carried out using statistical software, MINITAB R14. A series of multiple regression analyses revealed that brick’s compressive strength and initial rate of absorption were the most significant predictor variables in the research. The results of simulation indicated that unit water absorption contributes to the strength reduction in masonry wall by 0.43 %. Comparison between all models showed that EC 6 and BS 5628 respectively underestimate the wall’s compressive strength by 31.69 % and 80.10 %, while Mann’s model overestimated the masonry strength by 14.41 % as compared to the developed model.